Flame-retardant biodegradable plastic as well as preparation method and application thereof
The formulation of a flame retardant biodegradable plastic through specific mixing and extrusion processes addresses compatibility and flame retardancy issues, enhancing mechanical properties and environmental safety, achieving improved toughness and flame resistance in biodegradable materials.
Patent Information
- Application Number
- CN202411562326.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2024-12-31
AI Technical Summary
Existing biodegradable plastics, such as polylactic acid (PLA) and polybutylene adipate/terephthalate (PBAT), face issues of poor compatibility, high cost, poor temperature resistance, low toughness, and inadequate flame retardancy, which are exacerbated by the use of halogen-based flame retardants that pose environmental hazards.
A flame retardant biodegradable plastic is formulated by melt mixing polylactic acid, polybutylene adipate/terephthalate, plasticized starch, inorganic filler, anti-dripping agent, lubricant, antioxidant, and chain extender, using a specific process involving a twin-screw extruder and controlled temperature zones to enhance compatibility and mechanical properties, and incorporating a phosphorus-based flame retardant like resorcinol bis(diphenyl phosphate) to improve flame resistance.
The resulting plastic exhibits improved toughness, temperature resistance, and flame retardancy, with a melt index of 7.2-10.3 g/10 min, density of 1.3-1.4 g/cm³, tensile strength of 20.1-30.3 MPa, elongation at break of 13.2-28.9%, and a flame retardant grade of 1.5-2.0 mmV0, while maintaining high biodegradability and reducing manufacturing costs.
Smart Images

Figure CN119220075A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of degradable plastics, and in particular to a flame-retardant biodegradable plastic and a preparation method and application thereof. Background Art
[0002] Plastics have the advantages of excellent mechanical properties, high chemical stability, and easy processing. They are widely used in packaging materials, disposable utensils, agricultural products, etc. However, the preparation of plastics consumes a lot of petroleum resources. At the same time, the "white pollution" generated by plastic products will cause serious environmental and biological hazards. Therefore, the development and promotion of environmentally friendly and degradable materials is an urgent need to alleviate the current environmental and ecological pressure.
[0003] Degradable plastics can be decomposed or degraded by microorganisms such as bacteria, algae, and fungi, and eventually converted into small molecules such as carbon dioxide and water, and the products are recycled by nature. Currently, degradable plastics such as polylactic acid (PLA), polybutylene adipate / terephthalate (PBAT), and polybutylene succinate (PBS) have been widely used and studied. Among them, PLA is made from corn or potato starch as raw materials and lactic acid produced by microbial fermentation as monomer polymerization. It has the advantages of abundant sources, good biocompatibility, and excellent mechanical properties. It is considered to be a promising biodegradable material.
[0004] As PLA is better understood and studied, it is found that it has shortcomings such as high brittleness, low melt strength, slow biodegradation rate, etc., and PLA is very easy to burn, and there is serious melt dripping during the combustion process, which poses a great safety hazard. Therefore, PLA needs to be toughened and flame-retarded to meet its needs in practical applications.
[0005] Usually, degradable synthetic polymer materials such as polybutylene adipate / terephthalate (PBAT), polybutylene succinate (PBS), polypropylene carbonate (PPC), etc., or natural polymer materials (such as starch, cellulose, protein, etc.) are added to PLA to combine the advantages of various materials and achieve the complementary performance of multiple materials, so as to achieve the purpose of strengthening and toughening PLA and ensure the degradation performance of PLA composite materials. PBAT is a thermoplastic biodegradable plastic. It is a copolymer of butylene adipate and butylene terephthalate. It has the characteristics of PBA and PBT. It has good ductility and elongation at break, as well as good heat resistance and impact resistance. In addition, it has excellent biodegradability and is one of the most popular and best degradable materials in the research of biodegradable plastics. The PBAT molecule has both a flexible long methylene chain and a rigid aromatic ring structure, which gives PBAT good toughness, impact resistance and heat resistance. Currently, many studies use PBAT to toughen PLA, but PLA and PBAT have poor compatibility. Tougheners, chain extenders, etc. are usually added to the system to improve the compatibility between the two.
[0006] Starch is found in high concentrations in plants such as corn, potatoes, and wheat. It is widely available, inexpensive, and completely biodegradable. Adding it to PLA can effectively increase the degradation rate of PLA composite materials while reducing the production cost of degradable materials.
[0007] For example, CN102604346 B discloses a biodegradable polylactic acid-starch flame retardant composite material and its preparation method. The flame retardant and degradable PLA composite material first modifies the starch surface by maleic anhydride, stearic acid, etc., and then extrudes the modified starch together with a mixture of PLA, flame retardant, etc. through a twin-screw extruder for granulation. However, there are a large number of hydroxyl groups in the starch matrix. After surface modification, its dispersibility and compatibility with PLA are improved to a certain extent, but starch as a filler still has problems such as poor fluidity and easy agglomeration; and the modification process is carried out in two steps, the modification process is complicated, the modification efficiency is low, and the processing cost is high. In order to improve the flame retardant properties of the material, flame retardants ammonium polyphosphate and melamine phosphate are introduced. These flame retardants are relatively expensive, resulting in increased material costs.
[0008] Bromine-based flame retardants are mainly used in traditional flame retardant systems. These halogen-based flame retardants will release a large amount of toxic hydrogen halide gas during combustion, which is harmful to the environment and human health. Compared with halogen-based flame retardants, halogen-free flame retardants such as phosphorus-based or nitrogen-based have the characteristics of low toxicity, low smoke, and low corrosion. Therefore, halogen-based flame retardants are gradually replaced by halogen-free flame retardants. Resorcinol bis(diphenyl phosphate) (RDP) is an organophosphorus flame retardant with high phosphorus content, good thermal stability, low volatility, and certain plasticizing and lubricating effects. In addition, RDP can promote the carbonization of polymers during combustion, while inhibiting free radical reactions, and play an efficient flame retardant role.
[0009] CN113754990A discloses a method for preparing a starch-based fully biodegradable material, which adopts a two-stage extrusion production process, connects the discharge port of a pre-plasticizing extruder with the middle section of a mixing extruder, first weighs a certain proportion of starch and a plasticizer and pre-plasticizes them through an extruder, then adds the starch melt that has been plasticized and dehydrated into the mixing extruder, and finally completes the mixing and dispersion of the degradable resin, processing aid and plasticized starch melt. This process avoids the phenomenon that the moisture in the starch causes the degradable resin to hydrolyze, thereby effectively improving the physical properties of the product, but the two-stage extrusion equipment has a complex structure, is difficult to operate, and has low production efficiency.
[0010] Based on the above-mentioned prior art, when starch is combined with polylactic acid (PLA), polybutylene adipate / terephthalate (PBAT) and other materials to prepare biodegradable plastics in the prior art, there are technical problems that need to be solved urgently, such as poor compatibility between the materials, difficult processing, high cost, poor temperature resistance of the plastic, poor toughness, and poor flame retardant effect. Summary of the invention
[0011] In order to solve the above technical problems, the present invention provides a flame retardant biodegradable plastic, which is made by melt mixing polylactic acid, polybutylene adipate / terephthalate, plasticized starch, inorganic filler, anti-dripping agent, lubricant, antioxidant and chain extender. The flame retardant biodegradable plastic has a melt index of 7.2-10.3 g / 10 min and a density of 1.3-1.4 g / cm 3 , tensile strength is 20.1-30.3MPa, elongation at break is 13.2-28.9%, flexural strength is 24.7-33.8MPa, flexural modulus is 1695.7-1926.2MPa, cantilever beam notched impact strength is 20.2-31.0kJ / m 2 , Rockwell hardness is 69.0-83.0HA, flame retardant grade is 1.5-2.0mmV0, and degradation rate is ≥69.8% after 90 days of biocomposting.
[0012] Furthermore, the test standard of the melt index is GB / T 3682; The test standard for density is GB / T 1033; The test standard for tensile strength is GB / T 1040; The test standard for elongation at break is GB / T 1040; The test standard for bending strength is GB / T 9341; The test standard for flexural modulus is GB / T 9341; The test standard for Izod notched impact strength is GB / T 1843; The test standard for Rockwell hardness is GB / T 3398; The flame retardant rating is tested according to UL 94.
[0013] Furthermore, the test standard for biocomposting degradation is: GB / T 19277.1-2011, the test conditions are: temperature 58±2°C, composting container volume 3.8L, and the reference sample is cellulose (chromatographically pure).
[0014] The calculation formula of the degradation rate is: degradation rate (%) = [cumulative CO2 generation of each container (g) - cumulative average CO2 generation of blank containers (g)] / theoretical CO2 release generated by flame retardant biodegradable plastics (g) × 100%.
[0015] Furthermore, in parts by weight, the components and contents of the flame retardant biodegradable plastic are as follows: Polylactic acid: 40-60 parts by weight; Polybutylene adipate / terephthalate: 0-20 parts by weight; Plasticized starch: 15-30 parts by weight; Inorganic filler: 3-10 parts by weight; Anti-dripping agent: 0.2-0.5 parts by weight; Lubricant: 0.3-1.0 parts by weight; Antioxidant: 0.1-0.5 parts by weight; Chain extender: 0.1-0.5 parts by weight.
[0016] Furthermore, the polylactic acid has a melt index of 30-40 g / 10 min, a tensile strength of ≥60 MPa, a flexural modulus of ≥3000 MPa, and a melting temperature of 170-180°C.
[0017] Furthermore, the melt index of the polybutylene adipate / terephthalate is 3-7 g / 10 min, and the notched cantilever beam impact strength is ≥20 kJ / m 2 , the melting temperature is 110-120℃.
[0018] Furthermore, the plasticized starch is prepared from starch and a flame retardant through hydrogen bonding.
[0019] Furthermore, the mass ratio of the starch to the flame retardant is (10-20): (5-10).
[0020] Furthermore, the starch is one or more of corn starch, glutinous rice starch, tapioca starch, potato starch, rice starch, and wheat starch.
[0021] Furthermore, the flame retardant is a phosphorus-based flame retardant.
[0022] Furthermore, the phosphorus-based flame retardant is one or more of resorcinol bis(diphenyl phosphate) (RDP) and tetraphenyl(bisphenol-A) diphosphate (BDP).
[0023] Furthermore, the inorganic filler is one or more of kaolin, calcium carbonate, calcium sulfate, talc, mica, and silicon dioxide.
[0024] Furthermore, the anti-drip agent is a polytetrafluoroethylene (PTFE) anti-drip agent.
[0025] Furthermore, the anti-dripping agent is polytetrafluoroethylene powder.
[0026] Furthermore, the lubricant is one or more of a silicone lubricant, a stearate lubricant, and a stearamide lubricant.
[0027] Furthermore, the antioxidant is one or more of hindered phenol antioxidants, amine antioxidants, and phosphite antioxidants.
[0028] Furthermore, the chain extender is one or more of peroxide compounds, isocyanate compounds, multifunctional epoxy compounds, and phosphate compounds; The present invention also provides a method for preparing the flame retardant biodegradable plastic, comprising the following steps: Step 1, polylactic acid, polybutylene adipate / terephthalate, inorganic filler, anti-dripping agent, lubricant, antioxidant, and chain extender are stirred and mixed to obtain a polylactic acid mixture; Step 2, plasticizing starch in the first five zones of the twin-screw extruder: feeding starch into the first zone of the twin-screw extruder and feeding flame retardant into the second zone, so that the flame retardant and starch are fully mixed and plasticized to generate plasticized starch; Step 3, blending the plasticized starch and the polylactic acid mixture in the sixth to eleventh zones of the twin-screw extruder: feeding the polylactic acid mixture prepared in step 1 into the sixth zone of the twin-screw extruder, mixing it with the plasticized starch after melt plasticization, extruding, cooling and granulating to obtain pellets; Step 4: vacuum-dry the pellets prepared in step 3 to obtain the flame-retardant biodegradable plastic.
[0029] Furthermore, the equipment used for stirring and mixing in step 1 is a mixer.
[0030] Furthermore, in step 1, the stirring speed is 100-400 r / min, the time is 1-3 min, and the temperature is room temperature.
[0031] Furthermore, in step 2, starch is fed through a loss-in-weight scale, and the flame retardant is fed through a liquid metering device.
[0032] Furthermore, in step 3, the polylactic acid mixture in step 1 is fed through a loss-in-weight scale.
[0033] Further, the processing temperature of the twin-screw extruder in step 2 and step 3 includes eleven temperature zones, wherein the temperature of the first temperature zone is 80-90°C, the temperature of the second temperature zone is 90-100°C, the temperature of the third temperature zone is 100-120°C, the temperature of the fourth temperature zone is 120-140°C, the temperature of the fifth temperature zone is 140-150°C, the temperature of the sixth temperature zone is 150-160°C, the temperature of the seventh temperature zone is 160-170°C, the temperature of the eighth temperature zone is 165-175°C, the temperature of the ninth temperature zone is 170-180°C, the temperature of the tenth temperature zone is 170-180°C, the temperature of the eleventh temperature zone is 170-180°C, the screw speed is 200-500 r / min, and the vacuum degree is controlled below -0.08MPa; The one temperature zone corresponds to one zone, the five temperature zones correspond to five zones, and the six temperature zones correspond to six zones.
[0034] Furthermore, the extruded strip extruded in step 3 is cooled in a 30° C. water tank, and the cooling time is not less than 30 seconds.
[0035] Furthermore, in step 4, the vacuum drying temperature is 60-90° C., the time is 6-10 h, and the vacuum degree is -0.1 MPa.
[0036] The present invention also provides a flame retardant biodegradable injection molded product, which is made by injection molding the flame retardant biodegradable plastic.
[0037] Furthermore, the equipment used for the injection molding is an injection molding machine.
[0038] Furthermore, the injection molding temperature is 160-180°C.
[0039] The invention also provides an electric cooker shell, which is made by injection molding the flame-retardant biodegradable plastic.
[0040] The beneficial effects of the present invention are: 1. The present invention significantly improves the toughness of flame-retardant biodegradable plastics by introducing a fully biodegradable polylactic acid (PLA) component with excellent heat resistance into a specific formula and using polybutylene adipate / terephthalate (PBAT) for toughening treatment. In addition, the invention introduces relatively low-priced starch as a filler, which can reduce the manufacturing cost of the material and significantly improve the cost competitiveness of the product. In addition, starch has a high carbon content and can act as a carbonizing agent during the combustion process of the material, effectively improving the flame retardant properties of the material. Resorcinol bis(diphenyl phosphate) (RDP) is an organophosphorus flame retardant. The phosphate groups on its surface can form hydrogen bonds with the hydroxyl groups on the starch surface, which can plasticize the starch during the heating extrusion process of the twin-screw extruder and improve the fluidity of the starch. At the same time, during the combustion of flame-retardant biodegradable plastics, the phosphorus-containing free radicals produced by the thermal decomposition of RDP can capture the •H free radicals and •OH free radicals in the combustion reaction, and play a role in gas phase flame retardancy by inhibiting free radical reactions. In addition, the compound of RDP and starch can have a condensed phase flame retardant effect, promote the rapid carbonization of the polymer during the combustion process, and play a good barrier role, thereby significantly improving the flame retardant properties of the material. 2. The present invention obtains a flame-retardant biodegradable plastic having the advantages of good compatibility, good temperature resistance, good toughness, good flame retardant effect, etc. by melt-mixing the raw materials in the specific formula of the present invention through specific process steps and feeding sequence, as well as the processing temperature of each zone of the twin-screw extruder during the melt processing. Compared with the shortcomings of the prior art containing polylactic acid (PLA) and polybutylene adipate / terephthalate (PBAT), the flame-retardant biodegradable plastic prepared by the present invention has a melt index of 7.2-10.3 g / 10 min and a density of 1.3-1.4 g / cm 3 , tensile strength is 20.1-30.3MPa, elongation at break is 13.2-28.9%, flexural strength is 24.7-33.8MPa, flexural modulus is 1695.7-1926.2MPa, cantilever beam notched impact strength is 20.2-31.0kJ / m 2 , Rockwell hardness is 69.0-83.0HA, flame retardant grade is 1.5-2.0mmV0, and degradation rate of biocomposting after 90 days is ≥69.8%; 3. The present invention can induce a cross-linking reaction between polybutylene adipate / terephthalate (PBAT) and polylactic acid (PLA) by adding a chain extender in a specific formula, thereby increasing the relative molecular mass of the polymer, further improving the compatibility between the two, and improving the mechanical properties and aging resistance of the material; 4. The flame-retardant biodegradable injection molded products prepared using the flame-retardant biodegradable plastic prepared by the present invention as raw materials have good flame retardancy and environmental protection, can effectively reduce the risk of fire, and provide users with a healthier and more comfortable living environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a picture of a vertical combustion test of the flame-retardant biodegradable plastic of Example 2 of the present invention; Figure 2 The curve showing the change of biodegradation percentage of the flame retardant biodegradable plastic over time in Example 2 of the present invention; Figure 3 The morphology comparison of the flame retardant biodegradable plastic of Example 2 of the present invention before and after degradation in biocompost; Figure 4 This is a process flow chart for preparing the flame retardant biodegradable plastic according to Example 2 of the present invention. DETAILED DESCRIPTION
[0042] In the following examples and comparative examples, the test standard of the melt index is GB / T 3682; The test standard for density is GB / T 1033; The test standard for tensile strength is GB / T 1040; The test standard for elongation at break is GB / T 1040; The test standard for bending strength is GB / T 9341; The test standard for flexural modulus is GB / T 9341; The test standard for Izod notched impact strength is GB / T 1843; The test standard for Rockwell hardness is GB / T 3398; The test standard for flame retardancy is UL 94; The test standard for biocomposting degradation is: GB / T 19277.1-2011, the test conditions are: temperature 58±2℃, composting container volume 3.8L, reference sample is cellulose (chromatographically pure). The calculation formula of the degradation rate is: degradation rate (%) = [accumulated CO2 generation of each container (g) - accumulated average CO2 generation of blank container (g)] / theoretical CO2 release generated by flame retardant biodegradable plastic (g) × 100% Example 1 The present embodiment provides a flame retardant biodegradable plastic, which is made by melt mixing polylactic acid, polybutylene adipate / terephthalate, plasticized starch, inorganic filler, anti-dripping agent, lubricant, antioxidant, and chain extender. The flame retardant biodegradable plastic has a melt index of 7.2 g / 10 min and a density of 1.4 g / cm3 , tensile strength is 30.3MPa, elongation at break is 13.2%, flexural strength is 33.8MPa, flexural modulus is 1926.2MPa, and cantilever beam notched impact strength is 20.2kJ / m 2 , Rockwell hardness is 83.0HA, flame retardant grade is 2.0mmV0, and degradation rate after 90 days of biocomposting is 69.8%.
[0043] In parts by weight, the components and contents of the flame retardant biodegradable plastic are as follows: Polylactic acid: 57.5 parts by weight; Polybutylene adipate / terephthalate: 20 parts by weight; Plasticized starch: 15 parts by weight; the plasticized starch is prepared from 10 parts by weight of corn starch and 5 parts by weight of flame retardant resorcinol bis(diphenyl phosphate) (RDP) through hydrogen bonding; The inorganic filler is talcum powder: 5 parts by weight; The anti-dripping agent is polytetrafluoroethylene powder: 0.5 parts by weight; The lubricant is calcium stearate CAST: 1.0 part by weight; The antioxidants include: main antioxidant 1010: 0.2 weight part; auxiliary antioxidant 168: 0.3 weight part; The chain extender is BASF ADR: 0.5 parts by weight.
[0044] This embodiment also provides a method for preparing a flame retardant biodegradable plastic, comprising the following steps: Step 1, polylactic acid, polybutylene adipate / terephthalate, inorganic filler, anti-dripping agent, lubricant, antioxidant, and chain extender are stirred and mixed uniformly in a mixer, wherein the stirring speed is 400 r / min, the time is 2 min, and the temperature is room temperature to obtain a polylactic acid mixture; Step 2, plasticizing starch in the first five zones of the twin-screw extruder: feeding starch into the first zone of the twin-screw extruder through a weight loss scale, and feeding flame retardant into the second zone through a liquid metering device, so that the flame retardant and starch can be fully mixed and plasticized to generate plasticized starch; Step 3, blending the plasticized starch and the polylactic acid mixture in the sixth to eleventh zones of the twin-screw extruder: feeding the polylactic acid mixture prepared in step 1 into the sixth zone of the twin-screw extruder through a loss-in-weight scale, mixing it with the plasticized starch after melt plasticization, extruding, cooling and granulating, and cooling the extruded strips in a 30° C. water tank for a cooling time of not less than 30 seconds to obtain pellets; Wherein, the processing temperature of the twin-screw extruder in step 2 and step 3 includes eleven temperature zones, wherein the temperature of one temperature zone is controlled at 80-90°C, the temperature of the second temperature zone is controlled at 90-100°C, the temperature of the third temperature zone is controlled at 100-120°C, the temperature of the fourth temperature zone is controlled at 120-140°C, the temperature of the fifth temperature zone is controlled at 140-150°C, the temperature of the sixth temperature zone is controlled at 150-160°C, the temperature of the seventh temperature zone is controlled at 160-170°C, the temperature of the eighth temperature zone is controlled at 165-175°C, the temperature of the ninth temperature zone is controlled at 170-180°C, the temperature of the tenth temperature zone is controlled at 170-180°C, the temperature of the eleventh temperature zone is controlled at 170-180°C, the screw speed is controlled at 200-500 r / min, and the vacuum degree is controlled below -0.08MPa; Step 4: Dry the pellets prepared in step 3 in a vacuum drying oven at 70° C. for 8 hours to obtain the flame retardant biodegradable plastic.
[0045] This embodiment also provides a flame retardant biodegradable injection molded product prepared from the above-mentioned flame retardant biodegradable plastic, wherein the equipment used for injection molding is an injection molding machine, and the temperature is controlled within 160-180°C to obtain a flame retardant biodegradable injection molded product, which is used to prepare a flame retardant biodegradable rice cooker shell with good flame retardancy and environmental protection, can effectively reduce the risk of fire, and provide users with a healthier and more comfortable living environment.
[0046] Example 2 This embodiment provides a flame retardant biodegradable plastic, which is made by melt mixing polylactic acid, polybutylene adipate / terephthalate, plasticized starch, inorganic filler, anti-dripping agent, lubricant, antioxidant, and chain extender. A vertical combustion test is performed on the flame retardant biodegradable plastic in this embodiment. The test results are as follows: Figure 1 As shown, it is proved that the flame retardant biodegradable plastic has good flame retardant effect.
[0047] The flame retardant biodegradable plastic has a melt index of 8.9 g / 10 min and a density of 1.3 g / cm 3 , tensile strength is 26.6MPa, elongation at break is 26.7%, flexural strength is 29.3MPa, flexural modulus is 1877.3MPa, and cantilever beam notched impact strength is 29.3kJ / m 2 , Rockwell hardness is 78.0HA, and flame retardancy is 1.5mmV0. A curve is drawn for the average biodegradation percentage of the flame retardant biodegradable plastic (test material) biocompost 135 of this embodiment, as shown in FIG. Figure 2 As shown in FIG. 1 , the degradation rate after 90 days of biocomposting is 78.7%. The morphology of the flame retardant biodegradable plastic before and after degradation in the biocomposting is compared. Figure 3 shown.
[0048] In parts by weight, the components and contents of the flame retardant biodegradable plastic are as follows: Polylactic acid: 50 parts by weight; Polybutylene adipate / terephthalate: 20 parts by weight; Plasticized starch: 22.5 parts by weight; the plasticized starch is prepared by hydrogen bonding of 15 parts by weight of corn starch and 7.5 parts by weight of flame retardant resorcinol bis(diphenyl phosphate) (RDP); The inorganic filler is talcum powder: 5 parts by weight; The anti-dripping agent is polytetrafluoroethylene powder: 0.5 parts by weight; The lubricant is calcium stearate CAST: 1.0 part by weight; The antioxidants include: main antioxidant 1010: 0.2 weight part; auxiliary antioxidant 168: 0.3 weight part; The chain extender is BASF ADR: 0.5 parts by weight.
[0049] This embodiment also provides a method for preparing a flame retardant biodegradable plastic, comprising the following steps, the process flow chart is as follows: Figure 4 As shown: Step 1, polylactic acid, polybutylene adipate / terephthalate, inorganic filler, anti-dripping agent, lubricant, antioxidant, and chain extender are stirred and mixed uniformly in a mixer, wherein the stirring speed is 400 r / min, the time is 2 min, and the temperature is room temperature to obtain a polylactic acid mixture (PLA mixture); Step 2: Plasticizing starch in the first five zones of the twin-screw extruder: feeding starch into the first zone (main feeding port) of the twin-screw extruder through a loss-in-weight scale, and feeding flame retardant (RDP) into the second zone through a liquid metering device, so that the flame retardant and starch can be fully mixed and plasticized to generate plasticized starch; Step 3, blending the plasticized starch and the polylactic acid mixture in the sixth to eleventh zones of the twin-screw extruder: feeding the polylactic acid mixture prepared in step 1 into the sixth zone of the twin-screw extruder through a loss-in-weight scale, mixing it with the plasticized starch after melt plasticization, extruding, cooling and granulating, and cooling the extruded strips in a 30° C. water tank for a cooling time of not less than 30 seconds to obtain pellets; Wherein, the processing temperature of the twin-screw extruder in step 2 and step 3 includes eleven temperature zones, wherein the temperature of one temperature zone is controlled at 80-90°C, the temperature of the second temperature zone is controlled at 90-100°C, the temperature of the third temperature zone is controlled at 100-120°C, the temperature of the fourth temperature zone is controlled at 120-140°C, the temperature of the fifth temperature zone is controlled at 140-150°C, the temperature of the sixth temperature zone is controlled at 150-160°C, the temperature of the seventh temperature zone is controlled at 160-170°C, the temperature of the eighth temperature zone is controlled at 165-175°C, the temperature of the ninth temperature zone is controlled at 170-180°C, the temperature of the tenth temperature zone is controlled at 170-180°C, the temperature of the eleventh temperature zone is controlled at 170-180°C, the screw speed is controlled at 200-500 r / min, and the vacuum degree is controlled below -0.08MPa; Step 4: Dry the pellets prepared in step 3 in a vacuum drying oven at 70° C. for 8 hours to obtain the flame retardant biodegradable plastic.
[0050] This embodiment also provides a flame retardant biodegradable injection molded product prepared from the above-mentioned flame retardant biodegradable plastic, wherein the equipment used for injection molding is an injection molding machine, and the temperature is controlled within 160-180°C to obtain a flame retardant biodegradable injection molded product, which is used to prepare a flame retardant biodegradable rice cooker shell with good flame retardancy and environmental protection, can effectively reduce the risk of fire, and provide users with a healthier and more comfortable living environment.
[0051] Example 3 The present embodiment provides a flame retardant biodegradable plastic, which is made by melt mixing polylactic acid, polybutylene adipate / terephthalate, plasticized starch, inorganic filler, anti-dripping agent, lubricant, antioxidant, and chain extender. The flame retardant biodegradable plastic has a melt index of 10.3 g / 10 min and a density of 1.3 g / cm 3 , tensile strength is 20.1MPa, elongation at break is 28.9%, flexural strength is 24.7MPa, flexural modulus is 1695.7MPa, and cantilever beam notched impact strength is 31.0kJ / m 2 , Rockwell hardness is 69.0HA, flame retardant grade is 1.5mmV0, and degradation rate after 90 days of biocomposting is 81.7%.
[0052] In parts by weight, the components and contents of the flame retardant biodegradable plastic are as follows: Polylactic acid: 42.5 parts by weight; Polybutylene adipate / terephthalate: 20 parts by weight; Plasticized starch: 30 parts by weight; the plasticized starch is prepared by hydrogen bonding of 20 parts by weight of corn starch and 10 parts by weight of flame retardant resorcinol bis(diphenyl phosphate) (RDP); The inorganic filler is talcum powder: 5 parts by weight; The anti-dripping agent is polytetrafluoroethylene powder: 0.5 parts by weight; The lubricant is calcium stearate CAST: 1.0 part by weight; The antioxidants include: main antioxidant 1010: 0.2 weight part; auxiliary antioxidant 168: 0.3 weight part; The chain extender is BASF ADR: 0.5 parts by weight.
[0053] This embodiment also provides a method for preparing a flame retardant biodegradable plastic, comprising the following steps: Step 1, polylactic acid, polybutylene adipate / terephthalate, inorganic filler, anti-dripping agent, lubricant, antioxidant, and chain extender are stirred and mixed uniformly in a mixer, wherein the stirring speed is 400 r / min, the time is 2 min, and the temperature is room temperature to obtain a polylactic acid mixture; Step 2, plasticizing starch in the first five zones of the twin-screw extruder: feeding starch into the first zone of the twin-screw extruder through a weight loss scale, and feeding flame retardant into the second zone through a liquid metering device, so that the flame retardant and starch can be fully mixed and plasticized to generate plasticized starch; Step 3, blending the plasticized starch and the polylactic acid mixture in the sixth to eleventh zones of the twin-screw extruder: feeding the polylactic acid mixture prepared in step 1 into the sixth zone of the twin-screw extruder through a loss-in-weight scale, mixing it with the plasticized starch after melt plasticization, extruding, cooling and granulating, and cooling the extruded strips in a 30° C. water tank for a cooling time of not less than 30 seconds to obtain pellets; Wherein, the processing temperature of the twin-screw extruder in step 2 and step 3 includes eleven temperature zones, wherein the temperature of one temperature zone is controlled at 80-90°C, the temperature of the second temperature zone is controlled at 90-100°C, the temperature of the third temperature zone is controlled at 100-120°C, the temperature of the fourth temperature zone is controlled at 120-140°C, the temperature of the fifth temperature zone is controlled at 140-150°C, the temperature of the sixth temperature zone is controlled at 150-160°C, the temperature of the seventh temperature zone is controlled at 160-170°C, the temperature of the eighth temperature zone is controlled at 165-175°C, the temperature of the ninth temperature zone is controlled at 170-180°C, the temperature of the tenth temperature zone is controlled at 170-180°C, the temperature of the eleventh temperature zone is controlled at 170-180°C, the screw speed is controlled at 200-500 r / min, and the vacuum degree is controlled below -0.08MPa; Step 4: Dry the pellets prepared in step 3 in a vacuum drying oven at 70° C. for 8 hours to obtain the flame retardant biodegradable plastic.
[0054] This embodiment also provides a flame retardant biodegradable injection molded product prepared from the above-mentioned flame retardant biodegradable plastic, wherein the equipment used for injection molding is an injection molding machine, and the temperature is controlled within 160-180°C to obtain a flame retardant biodegradable injection molded product, which is used to prepare a flame retardant biodegradable rice cooker shell with good flame retardancy and environmental protection, can effectively reduce the risk of fire, and provide users with a healthier and more comfortable living environment.
[0055] Comparative Example 1 This comparative example provides a plastic. The raw materials for preparing the plastic do not include the flame retardant resorcinol bis(diphenyl phosphate) (RDP) relative to the embodiment, that is, the starch is not plasticized. The plastic is prepared by melt mixing polylactic acid, polybutylene adipate / terephthalate, starch, inorganic filler, anti-dripping agent, lubricant, antioxidant, and chain extender. The melt index of the plastic is 6.0 g / 10 min and the density is 1.4 g / cm 3 , tensile strength is 32.9MPa, elongation at break is 5.1%, flexural strength is 35.9MPa, flexural modulus is 2013.1MPa, and cantilever beam notched impact strength is 15.7kJ / m 2 , Rockwell hardness is 94.0HA, flame retardant grade is 3.0mmV0, and degradation rate after 90 days of biocomposting is 75.3%.
[0056] In parts by weight, the components and contents in the plastic are as follows: Polylactic acid: 57.5 parts by weight; Polybutylene adipate / terephthalate: 20 parts by weight; Starch: 15 parts by weight; The inorganic filler is talcum powder: 5 parts by weight; The anti-dripping agent is polytetrafluoroethylene powder: 0.5 parts by weight; The lubricant is calcium stearate CAST: 1.0 part by weight; The antioxidants include: main antioxidant 1010: 0.2 weight part; auxiliary antioxidant 168: 0.3 weight part; The chain extender is BASF ADR: 0.5 parts by weight.
[0057] This comparative example also provides a method for preparing a plastic, which comprises the following steps: Step 1, polylactic acid, polybutylene adipate / terephthalate, inorganic filler, anti-dripping agent, lubricant, antioxidant, and chain extender are stirred and mixed uniformly in a mixer, wherein the stirring speed is 400 r / min, the time is 2 min, and the temperature is room temperature to obtain a polylactic acid mixture; Step 2, directly adding starch: feeding starch into the first zone of the twin-screw extruder through a loss-in-weight scale; Step 3, blending the starch and polylactic acid mixture in the sixth to eleventh zones of the twin-screw extruder: feeding the polylactic acid mixture prepared in step 1 into the sixth zone of the twin-screw extruder through a weight loss scale, mixing it with the starch, extruding it, cooling it, and granulating it. The extruded extruded strips are cooled in a 30° C. water tank for a cooling time of not less than 30 seconds to obtain pellets; Wherein, the processing temperature of the twin-screw extruder in step 2 and step 3 includes eleven temperature zones, wherein the temperature of one temperature zone is controlled at 80-90°C, the temperature of the second temperature zone is controlled at 90-100°C, the temperature of the third temperature zone is controlled at 100-120°C, the temperature of the fourth temperature zone is controlled at 120-140°C, the temperature of the fifth temperature zone is controlled at 140-150°C, the temperature of the sixth temperature zone is controlled at 150-160°C, the temperature of the seventh temperature zone is controlled at 160-170°C, the temperature of the eighth temperature zone is controlled at 165-175°C, the temperature of the ninth temperature zone is controlled at 170-180°C, the temperature of the tenth temperature zone is controlled at 170-180°C, the temperature of the eleventh temperature zone is controlled at 170-180°C, the screw speed is controlled at 200-500 r / min, and the vacuum degree is controlled below -0.08MPa; Step 4: Dry the pellets prepared in step 3 in a vacuum drying oven at 70° C. for 8 hours to obtain the plastic.
[0058] Comparative Example 2 This comparative example provides a plastic. The raw material for preparing the plastic is bisphenol A-bis(diphenyl phosphate) (BDP), a flame retardant, relative to the example. The plastic is prepared by melt mixing polylactic acid, polybutylene adipate / terephthalate, starch mixture, inorganic filler, anti-dripping agent, lubricant, antioxidant, and chain extender. The melt index of the plastic is 10.1 g / 10 min and the density is 1.3 g / cm 3 , tensile strength is 29.8MPa, elongation at break is 19.8%, flexural strength is 31.4MPa, flexural modulus is 1903.2MPa, and cantilever beam notched impact strength is 20.8kJ / m 2 , Rockwell hardness is 77.0HA, flame retardant grade is 2.0mmV0, and degradation rate after 90 days of biocomposting is 72.4%.
[0059] In parts by weight, the components and contents in the plastic are as follows: Polylactic acid: 50 parts by weight; Polybutylene adipate / terephthalate: 20 parts by weight; Starch mixture: 22.5 parts by weight; the starch mixture is prepared from 15 parts by weight of corn starch and 7.5 parts by weight of flame retardant bisphenol A-bis(diphenyl phosphate) (BDP); The inorganic filler is talcum powder: 5 parts by weight; The anti-dripping agent is polytetrafluoroethylene powder: 0.5 parts by weight; The lubricant is calcium stearate CAST: 1.0 part by weight; The antioxidants include: main antioxidant 1010: 0.2 weight part; auxiliary antioxidant 168: 0.3 weight part; The chain extender is BASF ADR: 0.5 parts by weight.
[0060] This comparative example also provides a method for preparing a plastic, which comprises the following steps: Step 1, polylactic acid, polybutylene adipate / terephthalate, inorganic filler, anti-dripping agent, lubricant, antioxidant, and chain extender are stirred and mixed uniformly in a mixer, wherein the stirring speed is 400 r / min, the time is 2 min, and the temperature is room temperature to obtain a polylactic acid mixture; Step 2, preparing a starch mixture in the first five zones of the twin-screw extruder: feeding starch into the first zone of the twin-screw extruder through a weight loss scale, and feeding a flame retardant into the second zone through a liquid metering device, so that the flame retardant and the starch can be fully mixed to obtain a starch mixture; Step 3, blending the starch mixture and the polylactic acid mixture in the sixth to eleventh zones of the twin-screw extruder: feeding the polylactic acid mixture prepared in step 1 into the sixth zone of the twin-screw extruder through a weight loss scale, mixing it with the starch mixture after melt plasticization, extruding, cooling and granulating, and cooling the extruded strips in a 30° C. water tank for a cooling time of not less than 30 seconds to obtain pellets; Wherein, the processing temperature of the twin-screw extruder in step 2 and step 3 includes eleven temperature zones, wherein the temperature of one temperature zone is controlled at 80-90°C, the temperature of the second temperature zone is controlled at 90-100°C, the temperature of the third temperature zone is controlled at 100-120°C, the temperature of the fourth temperature zone is controlled at 120-140°C, the temperature of the fifth temperature zone is controlled at 140-150°C, the temperature of the sixth temperature zone is controlled at 150-160°C, the temperature of the seventh temperature zone is controlled at 160-170°C, the temperature of the eighth temperature zone is controlled at 165-175°C, the temperature of the ninth temperature zone is controlled at 170-180°C, the temperature of the tenth temperature zone is controlled at 170-180°C, the temperature of the eleventh temperature zone is controlled at 170-180°C, the screw speed is controlled at 200-500 r / min, and the vacuum degree is controlled below -0.08MPa; Step 4: Dry the pellets prepared in step 3 in a vacuum drying oven at 70° C. for 8 hours to obtain the plastic.
[0061] Comparative Example 3 The present comparative example provides a plastic, which is prepared by mixing polylactic acid, polybutylene adipate / terephthalate, starch, inorganic filler, anti-dripping agent, lubricant, antioxidant, chain extender and melt-mixing with flame retardant. The melt index of the plastic is 7.8 g / 10 min and the density is 1.3 g / cm 3 , tensile strength is 23.1MPa, elongation at break is 10.6%, flexural strength is 25.7MPa, flexural modulus is 1670.2MPa, and cantilever beam notched impact strength is 23.4kJ / m 2 , Rockwell hardness is 76.0HA, flame retardant grade is 2.0mmV0, and degradation rate after 90 days of biocomposting is 74.6%.
[0062] In parts by weight, the components and contents of the plastic are as follows: Polylactic acid: 50 parts by weight; Polybutylene adipate / terephthalate: 20 parts by weight; Starch: 15 parts by weight; Flame retardant resorcinol bis(diphenyl phosphate) (RDP): 7.5 parts by weight; The inorganic filler is talcum powder: 5 parts by weight; The anti-dripping agent is polytetrafluoroethylene powder: 0.5 parts by weight; The lubricant is calcium stearate CAST: 1.0 part by weight; The antioxidants include: main antioxidant 1010: 0.2 weight part; auxiliary antioxidant 168: 0.3 weight part; The chain extender is BASF ADR: 0.5 parts by weight.
[0063] This comparative example also provides a method for preparing a plastic, comprising the following steps: Step 1, polylactic acid, polybutylene adipate / terephthalate, starch, inorganic filler, anti-dripping agent, lubricant, antioxidant, and chain extender are stirred and mixed uniformly in a mixer, wherein the stirring speed is 400 r / min, the time is 2 min, and the temperature is room temperature to obtain a mixture; Step 2: Feed the mixture into the first zone of the twin-screw extruder through a weight loss scale, and feed the flame retardant into the second zone through a liquid metering device, so that the flame retardant and the mixture can be fully mixed, extruded, cooled and granulated, and the extruded extruded strips are cooled in a 30°C water tank for not less than 30 seconds to obtain pellets; Wherein, the processing temperature of the twin-screw extruder in step 2 includes eleven temperature zones, wherein the temperature of one temperature zone is controlled at 80-90°C, the temperature of the second temperature zone is controlled at 90-100°C, the temperature of the third temperature zone is controlled at 100-120°C, the temperature of the fourth temperature zone is controlled at 120-140°C, the temperature of the fifth temperature zone is controlled at 140-150°C, the temperature of the sixth temperature zone is controlled at 150-160°C, the temperature of the seventh temperature zone is controlled at 160-170°C, the temperature of the eighth temperature zone is controlled at 165-175°C, the temperature of the ninth temperature zone is controlled at 170-180°C, the temperature of the tenth temperature zone is controlled at 170-180°C, the temperature of the eleventh temperature zone is controlled at 170-180°C, the screw speed is controlled at 200-500 r / min, and the vacuum degree is controlled below -0.08MPa; Step 3: Dry the pellets prepared in step 2 in a vacuum drying oven at 70° C. for 8 hours to obtain the plastic.
[0064] Comparative Example 4 This comparative example provides a plastic. Compared with the preparation method of the embodiment, the feeding position of each substance in the twin-screw extruder is different. The plastic is made by melt mixing polylactic acid, polybutylene adipate / terephthalate, plasticized starch, inorganic filler, anti-dripping agent, lubricant, antioxidant, and chain extender. The melt index of the plastic is 5.6g / 10min and the density is 1.3g / cm 3 , tensile strength is 18.9MPa, elongation at break is 5.2%, flexural strength is 20.1MPa, flexural modulus is 1308.2MPa, and cantilever beam notched impact strength is 13.8kJ / m 2 , Rockwell hardness is 72.0HA, flame retardant grade is 3,0mmV0, and degradation rate after 90 days of biocomposting is 76.1%.
[0065] In parts by weight, the components and contents of the plastic are as follows: Polylactic acid: 50 parts by weight; Polybutylene adipate / terephthalate: 20 parts by weight; Plasticized starch: 22.5 parts by weight; the plasticized starch is prepared by hydrogen bonding of 15 parts by weight of corn starch and 7.5 parts by weight of flame retardant resorcinol bis(diphenyl phosphate) (RDP); The inorganic filler is talcum powder: 5 parts by weight; The anti-dripping agent is polytetrafluoroethylene powder: 0.5 parts by weight; The lubricant is calcium stearate CAST: 1.0 part by weight; The antioxidants include: main antioxidant 1010: 0.2 weight part; auxiliary antioxidant 168: 0.3 weight part; The chain extender is BASF ADR: 0.5 parts by weight.
[0066] This comparative example also provides a method for preparing a plastic comprising the following steps: Step 1, polylactic acid, polybutylene adipate / terephthalate, inorganic filler, anti-dripping agent, lubricant, antioxidant, and chain extender are stirred and mixed uniformly in a mixer, wherein the stirring speed is 400 r / min, the time is 2 min, and the temperature is room temperature to obtain a polylactic acid mixture; Step 2, feeding the polylactic acid mixture prepared in step 1 into the first zone of the twin-screw extruder through a weight loss scale, feeding starch into the sixth zone through a weight loss scale, and feeding the flame retardant into the seventh zone through a liquid metering device, mixing them together, extruding, cooling and granulating, and cooling the extruded strips through a 30° C. water tank for a cooling time of not less than 30 seconds to obtain pellets; Wherein, the processing temperature of the twin-screw extruder in step 2 includes eleven temperature zones, wherein the temperature of one temperature zone is controlled at 80-90°C, the temperature of the second temperature zone is controlled at 90-100°C, the temperature of the third temperature zone is controlled at 100-120°C, the temperature of the fourth temperature zone is controlled at 120-140°C, the temperature of the fifth temperature zone is controlled at 140-150°C, the temperature of the sixth temperature zone is controlled at 150-160°C, the temperature of the seventh temperature zone is controlled at 160-170°C, the temperature of the eighth temperature zone is controlled at 165-175°C, the temperature of the ninth temperature zone is controlled at 170-180°C, the temperature of the tenth temperature zone is controlled at 170-180°C, the temperature of the eleventh temperature zone is controlled at 170-180°C, the screw speed is controlled at 200-500 r / min, and the vacuum degree is controlled below -0.08MPa; Step 3: Dry the pellets prepared in step 2 in a vacuum drying oven at 70° C. for 8 hours to obtain the plastic.
[0067] From the above comparison, it can be seen that Example 2 has the best comprehensive performance, which shows that by adding an appropriate amount of starch and RDP to the PLA / PBAT system, the toughness of the material can be significantly improved, the strength of the material can be guaranteed, and the material can be endowed with excellent flame retardant properties. Compared with Example 2, RDP was not added in Comparative Example 1, and the flame retardant grade and impact properties of the material decreased significantly, indicating that the raw materials plus starch basically have no flame retardant properties, and the compatibility of starch and polymer matrix directly blended is poor; Comparative Example 2 uses BDP as a flame retardant, and the flame retardant properties of the material are not as good as those of Example 2, indicating that the addition of RDP significantly improves the flame retardant properties of the material; Comparative Example 3 fully mixes the raw materials for feeding, and its mechanical properties and flame retardant properties are reduced compared with Example 2, indicating that compared with partition feeding, fully mixed feeding easily causes starch to be coated by PLA / PBAT raw materials with higher viscosity, resulting in uneven dispersion and poor plasticization; Comparative Example 4 feeds the polylactic acid mixture into one zone, starch is fed from the sixth zone, and the flame retardant is fed from the seventh zone, and its mechanical properties and flame retardant properties are significantly reduced, indicating that the rear screw is too short to completely plasticize the starch, resulting in poor compatibility with the matrix and poor material plasticization.
[0068] In summary, the present invention significantly improves the toughness of flame-retardant biodegradable plastics by introducing a fully biodegradable polylactic acid (PLA) component with excellent heat resistance into a specific formula and using polybutylene adipate / terephthalate (PBAT) for toughening treatment. In addition, the invention introduces relatively low-priced starch as a filler, which can reduce the manufacturing cost of the material and significantly improve the cost competitiveness of the product. In addition, starch has a high carbon content and can act as a carbonizing agent during the combustion process of the material, effectively improving the flame retardant properties of the material. Resorcinol bis(diphenyl phosphate) (RDP) is an organophosphorus flame retardant. The phosphate groups on its surface can form hydrogen bonds with the hydroxyl groups on the surface of starch, which can plasticize the starch during the heating extrusion process of the twin-screw extruder and improve the fluidity of the starch. At the same time, during the combustion of flame-retardant biodegradable plastics, the phosphorus-containing free radicals produced by the thermal decomposition of RDP can capture the •H free radicals and •OH free radicals in the combustion reaction, and play a role in gas phase flame retardancy by inhibiting the free radical reaction. In addition, the compound of RDP and starch can have a condensed phase flame retardant effect, promote the rapid carbonization of the polymer during the combustion process, and play a good barrier role, thereby significantly improving the flame retardant properties of the material.
[0069] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A flame retardant biodegradable plastic, characterized in that: The flame retardant biodegradable plastic is prepared by melt mixing polylactic acid, polybutylene adipate / terephthalate, plasticized starch, inorganic filler, anti-dripping agent, lubricant, antioxidant and chain extender. The flame retardant biodegradable plastic has a melt index of 7.2-10.3 g / 10 min and a density of 1.3-1.4 g / cm 3 , tensile strength is 20.1-30.3MPa, elongation at break is 13.2-28.9%, flexural strength is 24.7-33.8MPa, flexural modulus is 1695.7-1926.2MPa, cantilever beam notched impact strength is 20.2-31.0kJ / m 2 , Rockwell hardness is 69.0-83.0HA, flame retardant grade is 1.5-2.0mmV0, and degradation rate is ≥69.8% after 90 days of biocomposting.
2. The flame retardant biodegradable plastic according to claim 1, characterized in that: In parts by weight, the components and contents of the flame retardant biodegradable plastic are as follows: Polylactic acid: 40-60 parts by weight; Polybutylene adipate / terephthalate: 0-20 parts by weight; Plasticized starch: 15-30 parts by weight; Inorganic filler: 3-10 parts by weight; Anti-dripping agent: 0.2-0.5 parts by weight; Lubricant: 0.3-1.0 parts by weight; Antioxidant: 0.1-0.5 parts by weight; Chain extender: 0.1-0.5 parts by weight.
3. The flame retardant biodegradable plastic according to claim 2, characterized in that: The plasticized starch is prepared from starch and a flame retardant through hydrogen bonding.
4. The flame retardant biodegradable plastic according to claim 3, characterized in that: The mass ratio of the starch to the flame retardant is (10-20):(5-10).
5. A method for preparing the flame retardant biodegradable plastic according to any one of claims 1 to 4, characterized in that: The steps include: Step 1, polylactic acid, polybutylene adipate / terephthalate, inorganic filler, anti-dripping agent, lubricant, antioxidant, and chain extender are stirred and mixed to obtain a polylactic acid mixture; Step 2, plasticizing starch in the first five zones of the twin-screw extruder: feeding starch into the first zone of the twin-screw extruder and feeding flame retardant into the second zone, so that the flame retardant and starch are fully mixed and plasticized to generate plasticized starch; Step 3, blending the plasticized starch and the polylactic acid mixture in the sixth to eleventh zones of the twin-screw extruder: feeding the polylactic acid mixture prepared in step 1 into the sixth zone of the twin-screw extruder, mixing it with the plasticized starch after melt plasticization, extruding, cooling and granulating to obtain pellets; Step 4: vacuum-dry the pellets prepared in step 3 to obtain the flame-retardant biodegradable plastic.
6. The method for preparing the flame retardant biodegradable plastic according to claim 5, characterized in that: In step 1, the stirring speed is 100-400 r / min, the time is 1-3 min, and the temperature is room temperature.
7. The method for preparing the flame retardant biodegradable plastic according to claim 5, characterized in that: The processing temperature of the twin-screw extruder in step 2 and step 3 includes eleven temperature zones, wherein the temperature of one temperature zone is 80-90°C, the temperature of two temperature zones is 90-100°C, the temperature of three temperature zones is 100-120°C, the temperature of four temperature zones is 120-140°C, the temperature of five temperature zones is 140-150°C, the temperature of six temperature zones is 150-160°C, the temperature of seven temperature zones is 160-170°C, the temperature of eight temperature zones is 165-175°C, the temperature of nine temperature zones is 170-180°C, the temperature of ten temperature zones is 170-180°C, the temperature of eleven temperature zones is 170-180°C, the screw speed is 200-500 r / min, and the vacuum degree is controlled below -0.08MPa.
8. A flame retardant biodegradable injection molded product, characterized in that: The product is made by injection molding the flame retardant biodegradable plastic according to any one of claims 1 to 4.
9. The flame retardant biodegradable injection molded product according to claim 8, characterized in that: The equipment used in the injection molding is an injection molding machine.
10. A rice cooker housing, characterized in that: The rice cooker shell is made of the flame-retardant biodegradable plastic according to any one of claims 1 to 4.
Citation Information
Cited By
Seawater degradable plastic packaging barrel and preparation method thereof
CN121537762A
A seawater-degradable plastic packaging barrel and a preparation method thereof
CN121537762B